Differentiating Apical and Basal Left Ventricular Aneurysms Using Sphericity Index: A Clinical Study - Slobodan Tomić; Stefan Veljković; Armin Šljivo; Dragana Radoičić; Goran Lončar; Milovan Bojić (Medicina)
Background and Objectives: Left ventricular aneurysm (LVA) causes geometric changes, including reduced systolic function and a more spherical shape, which is quantified by the sphericity index (SI), the ratio of the short to long axis in the apical four-chamber view. This study aimed to assess SI’s value in A-LVA and B-LVA, identify influencing factors, and evaluate its clinical relevance. Materials and Methods: This clinical study included 54 patients with post-infarction LVA and used echocardiography to determine LVA locations (A-LVA near the apex and B-LVA in the basal segments), with SI and other echocardiographic measures assessed in both systole and diastole for the entire cohort and stratified by A-LVA and B-LVA groups. Results: Among the 54 patients, 41 had A-LVA and 13 had B-LVA. The mean SI was 0.55 in diastole and 0.47 in systole for the cohort. Patients with A-LVA had a mean SI of 0.51 in diastole and 0.44 in systole, while B-LVA patients exhibited significantly higher SI values, with 0.65 in diastole and 0.57 in systole, due to lower long-axis (L) values in both phases. The mean left ventricular ejection fraction (EF) was 23.95% in A-LVA and 30.85% in B-LVA, with no significant difference. However, apical aneurysms were larger (greater LVAV and LVAA) and more significantly reduced functional myocardium. LVEDV, LVESV, LVEDA, and LVESA did not differ significantly between A-LVA and B-LVA. In cases of severe mitral regurgitation (MR), SI was notably higher (0.75 in diastole) due to a marked reduction in the L axis. Conclusions: SI is key in differentiating A-LVA and B-LVA on echocardiography. B-LVA has lower volume and area values, but similar aneurysm and left ventricular volumes and EF. Higher SI in B-LVA is due to a reduced L-axis, and is worsened by severe mitral regurgitation (MR). Surgical ventricular reconstruction (SVR) compensates for L-axis reduction, with preservation of the L axis critical for achieving a more physiological shape. SI thus serves as a marker for left ventricular geometry and surgical outcomes.